Hellboy and the B.P.R.D. 1952-1954 - Mignola, Mike; Arcudi, John; Roberson, Chris (Dark Horse Books, 2024)
"Hellboy's career in the B.P.R.D. kicks off in this collection of his earliest missions! The organization's most famous agent finds his footing in the world of paranormal investigation, cutting his teeth on cases all over the world in this collection of stories set from 1952-1954"--